2000
DOI: 10.3102/00346543070001003
|View full text |Cite
|
Sign up to set email alerts
|

Cross Cultural Competency and Multicultural Teacher Education

Abstract: Teachers require support as they face the challenge of effectively teaching diverse students in their classrooms. Teacher-educators have used various methods to foster change in teachers' thinking, attitudes, and behaviors regarding cultural diversity, but these efforts have produced mixed results because they often focused on content rather the process of cross-cutural learning. The purpose of this review is to examine three process-oriented models that have been used to describe and measure the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
0
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(146 citation statements)
references
References 26 publications
4
136
0
6
Order By: Relevance
“…Interventions such as the one described have the potential to effectively produce thoughtful counselors who are prepared to work in a complex, rapidly-changing environment. Researchers (e.g., McAllsiter and Irvine 2000;Sue et al 1992) have suggested that in order for professionals to be effective with diverse populations, they must first be aware of their own racial and cultural biases. Rest and Narvaez (1994) referred to this awareness as ethical sensitivity, a necessary but not sufficient first step towards moral behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions such as the one described have the potential to effectively produce thoughtful counselors who are prepared to work in a complex, rapidly-changing environment. Researchers (e.g., McAllsiter and Irvine 2000;Sue et al 1992) have suggested that in order for professionals to be effective with diverse populations, they must first be aware of their own racial and cultural biases. Rest and Narvaez (1994) referred to this awareness as ethical sensitivity, a necessary but not sufficient first step towards moral behavior.…”
Section: Discussionmentioning
confidence: 99%
“…But for the other three Gee categories, in fairly short order the contributors exhibited shifts in their identities. Concomitantly, their trajectories appeared to become more in line with being cultural competent teachers (McAllister and Irvine 2000). This reveals how each individual is an ongoing project and suggest that challenges still await them as they navigate their way as White professionals who work in culturally and linguistically diverse settings (Ellsworth 1997).…”
Section: Resultsmentioning
confidence: 94%
“…Borrowing from Marilyn Cochran-Smith's journey metaphor (2004), there were plenty of detours, delays, and distractions as the contributors contemplated the ideals of culturally responsive pedagogy. In contrast to the master narrative that ascribes to preservice teachers an inherent inability to become effective educators in contemporary diverse classrooms, their stories revealed how inexperience is not an insurmountable barrier to becoming engaged in more culturally competent commitments toward teaching (McAllister and Irvine 2000). Instead, a more generous perspective for teacher educators is to recognize the assets such individuals bring to their teacher preparation courses rather than perpetuating implicit assumptions about deficiencies.…”
mentioning
confidence: 72%
“…Gorski (2009) examined the syllabi from multicultural teacher education courses taught across the United States and revealed that most of the courses were designed to prepare pre-service teachers with pragmatic skills and personal awareness. McAllister and Irvine (2000) examined three process-oriented models that have been used to describe and measure the development of racial identity and cross-cultural competence, including Helms' model of racial identity development, Banks' Typology of Ethnicity, and Bennet's Developmental Model of Intercultural Sensitivity. McAllister and Irvine concluded that teacher educators should use various methods to www.ccsenet.org/ies International Education Studies Vol.…”
Section: Developing Multicultural Education For Pre-service Teachersmentioning
confidence: 99%